Assessment and Quantification of Damages in Private and Public International Law: an Overview - Kałduński, Marcin (Polish Review of International and European Law, 2022)
This piece is a modest tribute to Professor Gilas who has long been the author’s tutor during the author’s academic career. Its purpose is to concisely describe how international law on damages has evolved, taking into particular account the jurisprudence of international courts and tribunals as well as domestic courts. The topic of damages is important in practice, but seems to be neglected in the doctrine. The author thus wishes to make an overview on the assessment and quantification of damages. To this end, the article starts with a presentation of basic principles to discuss further the burden and standard of proof, entitlement to damages, assessment of amount of damages, quantification of damages, reduction of damages, including causation, prohibition of speculative damages, contributory fault, foreseeability, mitigation and the prohibition of double recovery. Article concludes with final observations.